2015
DOI: 10.1002/lsm.22414
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound stimulates MC3T3-E1 cell proliferation through the activation of NF-κB1, p38α, and mTOR

Abstract: Therapeutic ultrasound, with frequency of 1 MHz, intensity of 0.2 W/cm(2) (SATA) and pulsed mode, for 30 minutes, was able to increase the proliferation of preosteoblast-like bone cells. This effect was mediated by a calcium influx, with a consequent activation of the mTOR pathway, through increased NF-κB1 and p38α.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…A previous study also suggested that LIPUS did not have any changes in temperature. The main effect of LIPUS could be caused by “nonthermal effects,” such as cavitation effects and microstreaming effects …”
Section: Discussionmentioning
confidence: 99%
“…A previous study also suggested that LIPUS did not have any changes in temperature. The main effect of LIPUS could be caused by “nonthermal effects,” such as cavitation effects and microstreaming effects …”
Section: Discussionmentioning
confidence: 99%
“…ERK1/2 pathway involvement was previously observed 8,9 . The p38 MAPK pathway, which is another significant subgroup of the MAPK superfamily, was involved in the response to proliferation-inducing stimuli in an osteoblastic cell line 11 . In addition, according to Sinfield's study, the p38α subtype facilitates IL-1-induced IL-6 secretion by human cardiac fibroblasts 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we investigated IκBα and pp65 as key factors to indirectly assess NF-κB activation. Notably, MAPKs, including ERK and p38, are typically involved in bone metabolism in combination with NF-κB pathway activation 11,19 . Both pathways are associated with the inhibition of osteoclast formation by K7 in mouse bone marrow-derived macrophages 19 as well as the therapeutic ultrasound-induced proliferation of MC3T3-E1 cells 11 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations